1991
DOI: 10.1093/jac/28.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftazidime in patients with liver cirrhosis and ascites

Abstract: The pharmacokinetics of ceftazidime were studied in 18 male individuals, including six healthy volunteers and 12 patients with liver cirrhosis and ascites. Each participant received 1 g of ceftazidime as a single intravenous bolus injection. The elimination half-life was longer in cirrhotic than in control patients (5.40 +/- 1.02 h) vs. (1.98 +/- 0.24 h), P less than 0.01; probably due to slow return from the ascitic compartment. Nevertheless, total body clearance did not differ significantly between the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…These results are consistent with the hypothesis that ceftazidime could diffuse into the oedematous fluid, which could act as a reservoir from which ceftazidime returns slowly to the circulation. Such a phenomenon has been described for ceftazidime in patients with ascites [7]. The two-compartment model is compatible with this hypothesis.…”
Section: Figuresupporting
confidence: 78%
“…These results are consistent with the hypothesis that ceftazidime could diffuse into the oedematous fluid, which could act as a reservoir from which ceftazidime returns slowly to the circulation. Such a phenomenon has been described for ceftazidime in patients with ascites [7]. The two-compartment model is compatible with this hypothesis.…”
Section: Figuresupporting
confidence: 78%
“…Approximately 1% of ceftazidime clearance is through biliary excretion. Previous studies in chronic liver failure and in cirrhosis have shown changes in volume of distribution resulting in shortened elimination half-times with no overall change in total body clearance [35,36]. There was no evidence for signi®cant nonrenal clearance in this study [37].…”
Section: Discussioncontrasting
confidence: 44%
“…Approximately 1% of ceftazidime clearance is through biliary excretion. Previous studies in chronic liver failure and in cirrhosis have shown changes in volume of distribution resulting in shortened elimination half‐times with no overall change in total body clearance [35, 36]. There was no evidence for significant nonrenal clearance in this study [37].…”
Section: Discussionmentioning
confidence: 45%